Growth of calcium phosphates on magnesium substrates for corrosion control in biomedical applications via immersion techniques1. Issue 1 (22nd October 2012) - Shadanbaz, Shaylin; Walker, Jemimah; Staiger, Mark P.; Dias, George J.; Pietak, Alexis
Abstract: Magnesium (Mg) has been suggested as a revolutionary biodegradable replacement for current permanent metals used in orthopedic applications. Current investigations concentrate on the control of the corrosion rate to match bone healing. Calcium phosphate coatings have been a recent focus of these investigations through various coating protocols. Within this investigation, an in situ crystallization technique was utilized as an inexpensive and relatively simple method to produce a brushite and monetite coating on pure Mg. Coatings were characterized using energy dispersive spectroscopy, glancing angle X‐ray diffraction and field emission scanning electron microscopy. Corrosion protection properties of the coatings were assessed in physiological buffers, Earles balanced salt solution, minimum essential media, and minimum essential media containing serum albumin, over a 4‐week period. Using this novel coating protocol, our findings indicate brushite and monetite coated Mg to have significant corrosive protective effects when compared with its uncoated counterpart whilst maintaining high coating substrate adhesion, homogeneity, and reproducibility. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 162–172, 2013.